1995
DOI: 10.1109/96.386270
|View full text |Cite
|
Sign up to set email alerts
|

Electroless nickel/copper plating as a new bump metallization

Abstract: An electroless bumping method was developed both for fiip chip and TAB applications. Electroless NdCu plating is a maskless low-cost approach to bumping directly on aluminum bondpads. An immersion tin layer for coating and soldering is plated on the copper. Due to the high alkalinity (pH > 12) of electroless Cu baths, a thick Ni layer of about 7 Lt m is required on the aluminum for sealing. A shear strength of 180 cN and a contact resistance of less than 2 ma for the bumps were obtained. Because of the high ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…As ar esult, it has attracted much research interest and has found widespread use in chip interconnection technologies, especially as UBM for flip-chip applications. [1][2][3][4] The deadline for the switch to complete lead-free production in the electronic industry is coming closer. European Union (EU) directive 2002/95/EC of the European Parliament on the "Restriction of the Use of Certain Hazardous Substances" (RoHS) in electronical and electronic equipment requires that, after July 1, 2006, all of the electronic products in the EU be lead free and not contain other specified hazardous elements.…”
Section: Introductionmentioning
confidence: 99%
“…As ar esult, it has attracted much research interest and has found widespread use in chip interconnection technologies, especially as UBM for flip-chip applications. [1][2][3][4] The deadline for the switch to complete lead-free production in the electronic industry is coming closer. European Union (EU) directive 2002/95/EC of the European Parliament on the "Restriction of the Use of Certain Hazardous Substances" (RoHS) in electronical and electronic equipment requires that, after July 1, 2006, all of the electronic products in the EU be lead free and not contain other specified hazardous elements.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] During reflow soldering, the Au layer of ENIG dissolves into the molten solder, exposing the underlying Ni-P layer to the molten solder. Thereafter, Ni, Sn, and Cu react to form interfacial intermetallic compounds (IMCs), either (Cu,Ni) 6 Sn 5 or (Ni,Cu) 3 Sn 4 depending on the Cu content in the Sn-Ag-Cu (SAC) solder.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Due to the low resistivity of Cu, the conventional Al pad playing the role of conductor is replaced by a Cu pad in the Au/EN/Cu structure in current flip chip devices. 4 The oxidation of Cu could be avoided on account of the fact that the surface is covered by an under bump metallurgy (UBM) layer.…”
Section: Introductionmentioning
confidence: 99%